Potential benefits and challenges of simulation-based neonatal resuscitation competition: A survey analysis of provincial competition in China - Chenguang Xu; Qianshen Zhang; Fang Lin; Yihua Chen; Yin Xue; Wenjie Yan; Rong Zhou; Yuqian Yang; Po-Yin Cheung (Resuscitation Plus)
Background: Simulation-based neonatal resuscitation training has been implemented worldwide with good educational and clinical results. Simulation-based competition (SBC), as an innovative derivative of neonatal resuscitation training, has been practiced recently but its potential effectiveness and challenges of competition are rarely studied. We tested the hypothesis that after SBC, participants could improve compliance with NRP® algorithm and teamwork, achieve lower stress and higher confidence in neonatal resuscitation. Methods: In February 2023, 108 health care providers in 27 teams from different regional centres participated in provincial SBC. Each team consisted of 4 members (NICU physician [lead], NICU nurse, midwife and obstetrician). The teams were to complete a resuscitation scenario (16 min) and their performance was evaluated. All participants were encouraged to take part in a post-resuscitation questionnaire survey voluntarily immediately after the scenarios finished. Demographic characteristics and questionnaire results of participants were collected, including the confidence and perceived stress levels before and after the competition. Results: Ninety-eight (90.7%) participants completed the survey with 114 post-resuscitation questionnaire surveys. Participants perceived top benefits of SBC including improved compliance with NRP® algorithm, technical skills and teamwork, with the least benefit in improving self-confidence (vs. other benefits, P < 0.001). The confidence level did not change before and after the competition, whereas stress was reduced after the competition. Conclusions: Participants in SBC might be benefited with improved compliance with NRP® algorithm, technical skills and teamwork. However, the impact, influence and sustainability of these benefits are uncertain. Further research is needed to explore ways to improve self-confidence and decrease stress in neonatal resuscitation.